Incidence of bollworm complex in different events of Bt cotton - Ghante, Vijaykumar N; Chowdary, L Rajesh; Kumar, L Ranjith; Arunkumar, Hosamani; Bheemanna, M (Indian Journal of Plant Protection, 2020)
The incidence of cotton bollworms viz., Helicoverpa armigera, Earias vittella and Pectinophora gossypiella was studied in different events of Bt cotton approved for cultivation in India under natural/unprotected condition during 2009-10 and 2010-11. Results suggest that of the four events tested, Mon-15985 (BG II) appears to be more promising in protecting the crop against target pests. Whereas, the first generation single gene events viz., MON-531, Event 1 and GMF event were almost on par with each other in combating the bollworms.